Metyrapone in long-term management of Cushing's disease. Issue 6081 (23rd July 1977) - Jeffcoate, W J; Rees, L H; Tomlin, S; Jones, A E; Edwards, C R; Besser, G M
Abstract : Metyrapone was used in the long-term management of 13 patients with pituitary-dependent bilateral adrenal hyperplasia (Cushing's disease). The total length of treatment ranged from two to 66 months, with a mean of 21 months. The clinical features of the disease rapidly improved on metyrapone and this improvement was maintained. Although plasma ACTH concentrations rose in all patients, the increase was insufficient to overcome the adrenal blockade induced by the drug. Eight of the 13 patients had additional external pituitary irradiation as definitive treatment of their disease and one underwent a transfrontal hypophysectomy. Radiotherapy cured one patient, and after three years metyrapone was withdrawn. Slight hirsuties was noted in four of the seven women who received the drug for six months or more. A fifth woman had more severe hirsuties and this led to bilateral adrenalectomy. Other than hirsuties, side effects were few and the routine use of metyrapone is recommended as an adjunct to more definitive treatment in all patients who present with Cushing's syndrome, irrespective of aetiology.